2008
DOI: 10.1149/1.2897437
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Parylene-Metal-Parylene Thin Films in Saline

Abstract: In this paper, we study the corrosion behavior of parylene-metalparylene thin films using accelerated-lifetime soak tests. The samples under test are thin film resistors with a 200 nm layer of Au sandwiched by parylene-C on both sides, fabricated with parylenemetal skin technology. The samples are tested in hot saline both passively and actively, and different failure modes are observed using optical and electron-beam metrologies.Bubbles and delamination are first seen in the samples after 2 days of soaking un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…Failure modes of neural probes manifested as a loss of neural recording capability can be classified into those relating to device design [29, 35] (above the arrow) and foreign-body response [34, 36] (below the arrow). Design failure mechanisms include mechanical failure of interconnects [35], degradation and cracking of the insulation [219], electrode corrosion [220, 221] and delamination of probe layers [222]. Biological failure mechanisms include initial tissue damage during insertion [34, 37]; breach of the blood–brain barrier [41]; elastic mismatch and tissue micromotion [35, 38, 39]; disruption of glial networks [40]; formation of a glial scar; and neuronal death associated with the abovementioned factors, as well as with materials neurotoxicity [42] and chemical mismatch [34].…”
Section: Figure 1│mentioning
confidence: 99%
“…Failure modes of neural probes manifested as a loss of neural recording capability can be classified into those relating to device design [29, 35] (above the arrow) and foreign-body response [34, 36] (below the arrow). Design failure mechanisms include mechanical failure of interconnects [35], degradation and cracking of the insulation [219], electrode corrosion [220, 221] and delamination of probe layers [222]. Biological failure mechanisms include initial tissue damage during insertion [34, 37]; breach of the blood–brain barrier [41]; elastic mismatch and tissue micromotion [35, 38, 39]; disruption of glial networks [40]; formation of a glial scar; and neuronal death associated with the abovementioned factors, as well as with materials neurotoxicity [42] and chemical mismatch [34].…”
Section: Figure 1│mentioning
confidence: 99%
“…Previous studies [12] reported the formation of bubbles and delamination of thin Parylene-C films after just two days of soaking in saline solution. It is therefore important to investigate how the proposed plasma treatment influences the diffusion barrier properties of Parylene-C. For this purpose, a test setup similar to the one described by Op de Beeck et al [13] was used.…”
Section: Resultsmentioning
confidence: 99%
“…There are, however, reports of progressive degradation of the polymer insulation barrier properties when it is exposed to saline solution in a body-mimicking environment [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Parylene suffers from poor adhesion to itself and noble metals, such as gold and platinum, a considerable drawback in the implementation of Parylene for bioMEMS. The adhesion of Parylene devices, which consist of thin films of Parylene-metal-Parylene sandwiches, is compromised when devices are soaked in wet environments [ 58 , 60 , 66 , 68 , 69 ]. Weak adhesion can accelerate catastrophic failure of Parylene devices; as Parylene films lift off a substrate, voids form in which water vapor can condense, creating continuous paths of solution that create electrical shorts and drive further delamination ( Figure 6 ).…”
Section: Challengesmentioning
confidence: 99%